The Development of Natural Knowledge Science Learning Module to Improve Student Learning Achievement in Primary School - Sarjana Sarjana; Fadillah Fadillah; Indri Astuti (STKIP Singkawang, 2018)
This study aims to describe (1) the design of the development module for the preservation of living natural resources in the study of natural science; (2) the process of developing modules for the conservation of living natural resources in the learning of natural science; and (3) student learning about the preservation of living natural resources in the learning of Natural Sciences in the fourth grade of SD Negeri 01 Hulu Sungai. This research is descriptive qualitative research to study